Seismic risk of sliding ground-mounted rigid equipment. (1st February 2020) - Jaimes, Miguel A; Candia, Gabriel
Highlights: Formulation for risk assessment of sliding rigid equipment during earthquakes. Sliding risk assessment for four types of support conditions. Comprehensive earthquake risk assessment to sliding rigid equipment and contents. This work serves as a model for other types of equipment vulnerable to earthquakes. Abstract: This study discusses a general formulation for risk assessment of ground-mounted rigid sliding equipment and contents during earthquakes. The displacement and acceleration response of blocks during earthquakes and risk were examined for four types of support conditions: (1) equipment simply supported on a foundation; (2) equipment restrained to a fixed base; (3) equipment supported on a linear viscoelastic isolation system; and (4) equipment supported on a single concave spherical sliding (SCSS) isolation system. Because empirical fragility functions for sliding-dominated equipment remain insufficient, the present study relies on numerical analysis and a solid physical background to compute risk. These results should aid designers in the selection of appropriate support conditions or mitigation measures for rigid equipment and contents in seismic-prone regions. As an example, the seismic response of rigid equipment is illustrated using ground motions from the recent (2017) Mexico earthquakes, which damaged several pieces of equipment in the largest oil refinery in Mexico. Furthermore, the effects of site-to-source distance for sites located on firm soil are studied in detail, as the frequency content of these ground motions differ significantly and play a key role in the reliability of sliding blocks. The results of the seismic risk assessment show that low-frequency ground motions (i.e., far-field site) generally yield lower maximum and residual equipment displacements compared to those from high-frequency ground motions (i.e., near-source site). This investigation also concludes that the reliability of freestanding and base-isolated equipment in terms of maximum absolute block accelerations is higher than that of anchored equipment.